Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, G.; Baumhögger, Elmar; Elsner, A.; Fieback, K.; Morbach, A.; Paul, A.; Vrabec, J. (International Journal of Refrigeration)

Burst design and signal processing for the speed of sound measurement of fluids with the pulse-echo technique - Dubberke, Frithjof H.; Baumhögger, Elmar; Vrabec, Jadran (Review of Scientific Instruments)

Investigation of wear resistance of dry and cryogenic turned metastable austenitic steel shafts and dry turned and ground carburized steel shafts in the radial shaft seal ring system - Frölich, D.; Magyar, Balázs; Sauer, B.; Mayer, P.; Kirsch, B.; Aurich, J.C.; Skorupski, R.; Smaga, M.; Beck, T.; Eifler, D. (Wear)
The state of the art industrial manufacturing process to produce shafts as counter surfaces for radial shaft seal rings is plunge grinding. This process consists of three major steps. The blank is turned to a slight diameter-oversize followed by the heat treatment and the hard-finishing by plunge grinding. The geometric surface structures of the resulting shafts in general exhibit a stochastic distribution. These surface characteristics contribute to a reliable and stable sealing functionality. And the surface and subsurface hardness generally leads to a higher wear resistance of the shaft. Motivated by economic benefits and in order to achieve a compact production process for at least ten years, turning is investigated as an alternative manufacturing process. However due to the resulting lead structure on the shaft surface and the associated risk of leakage it has not become prevalent yet. In this paper turned shafts of the metastable austenitic steel AISI 347 (1.4550, X6CrNiNb1810) are investigated as alternative material for counter surfaces of radial shaft seal rings and compared to turned shafts of carburized AISI 5115 (1.7131, 16MnCr5). In addition to surfaces dry turned at room-temperature, cryogenic turned AISI 347 counter surfaces are analyzed. By applying cryogenic cooling, the formation of deformation-induced α′-martensite in the surface layer is possible during the turning process. Endurance tests in radial shaft seal ring test rigs are performed and complemented with detailed investigations of microstructure, micro-hardness and surface topography. The results are compared to results of state of the art ground AISI 5115 shafts.
Keywords: Radial shaft seal ring; Shaft surface; Cryogenic turning; Metastable austenitic steel; Deformation-induced martensite formation

Worm Gear Drives with High Efficiency - Oehler, M; Magyar, Balázs; Sauer, B (VDI-Berichte 2255)

Calculation of the efficiency of worm gear drives - Magyar, Balázs; Sauer, B (Power Transmission Engineering)

Wellendichtsysteme - Zimmer, Detmar; Nolte, Karsten; Hütte, Jürgen

Additive Manufacturing for Future Repair and Maintenance for the Aerospace Industry - Pottebaum, Jens; Lindemann, Christian-Friedrich; Deppe, Gereon; Koch, Rainer (Aviation in Europe - Innovating for Growth, Proceedings of the Sventh European Aeronautics Days)

Path Planning and Trajectory Optimization of Delta Parallel Robot - Shareef, Zeeshan

A multi-mechanism model for cutting simulations based on the concept of generalized stresses - Cheng, C.; Mahnken, Rolf (Computational Materials Science)

Comparison of hyperelastic micromorphic, micropolar and microstrain continua - Leismann, T.; Mahnken, Rolf (International Journal of Non-Linear Mechanics)

MESOSCOPIC MODELING OF THE RTM PROCESS FOR HOMOGENIZATION - Mahnken, Rolf; Dammann, Christian

Dual-based adaptive FEM for inelastic problems with standard FE implementations - Widany, K.-U.; Mahnken, Rolf (International Journal for Numerical Methods in Engineering)

Adaptive FEM with goal-oriented error estimation and an approximation of the dual problem for inelastic problems - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

Uncertainty quantification for linear elastic bodies with two fluctuating input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

A coupled phase-field - Cahn-Hilliard model for lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Transition from hyperelastic micromorphic to micropolar and microstrain continua - Leismann, Thorben; Mahnken, Rolf (PAMM)

Non-linear Stochastic Finite Element - Caylak, Ismail; Dridger, Alex; Mahnken, Rolf (PAMM)

Evaluation of different approaches for modeling phase transformations in machining simulation - Schulze, Volker; Uhlmann, Eckart; Mahnken, Rolf; Menzel, Andreas; Biermann, Dirk; Zabel, Andreas; Bollig, Patrick; Ivanov, Ivan M.; Cheng, Chun; Holtermann, Raphael; Bartel, Thorsten (Production Engineering)

A Novel Finite Element Approach to Modeling Hard Turning in Due Consideration of the Viscoplastic Asymmetry Effect - Uhlmann, Eckart; Mahnken, Rolf; Ivanov, Ivan Mitkov; Cheng, Chun (Procedia CIRP)

Simulation of lower bainitic transformation with the phase-field method considering carbide formation - Düsing, M.; Mahnken, Rolf (Computational Materials Science)